Quantification of selected anti - nutrients and bioactive compounds in African Bambara Groundnut (Vigna subterranea (L.) verdc.) - Atoyebi, J.O.; Osilesi, O.; Abberton, Michael T.; Adebawo, O.; Oyatomi, Olaniyi (Science and Education Publishing Co., Ltd., 2018)
Bioactive compounds in plants, being secondary metabolites are important phyto-chemicals, that form the basis of modern pharmacology and medical treatment because it has natural beneficial compounds such as in nutraceuticals, micronutrients e.t.c. Neglected legumes like Bambara groundnut (Vigna subterranea (L.) Verdc.) can serve as a high nutrient pulse and also as food supplements. However, despite the fact that Bambara groundnut contains these beneficial bioactive compounds, it also has some compounds, which on the other hand do exists as acute poisons and as contaminants in food, thus implying risks of adverse effects in animals and man. However, the ingested dosage of bioactive plant compounds is often a determinant for a decision as to whether the effect will be beneficial or adverse. Here, the work quantified and reported certain plant bioactive compounds and anti – nutrients in Bambara groundnut (Vigna subterranea (L.) Verdc.). The results of some bioactive compounds analysed in this pulse showed that the selected African accession had the highest amount of ascorbic acid of 29.90 mg / 100g in TVSu – 1822, while the least obtained, 11.24 mg / 100g was for TVSu – 1229. Oxalic acid was highest (0.0049 g/g) in TVSu – 1205, and the lowest (0.004 g/g) in TVSu – 1824. The amount of quantifiable cyanogenic glycosides (CNP) in form of hydrocyanic acid (HCN) was highest in TVSu – 1229 with 0.34 mg / 100g, and the least in accessions TVSu – 1824, TVSu – 553, TVSu – 1727 and TVSu – 922 with 0.05 mg / g. Also, the highest amount of trypsin inhibitors of 18.97 mg / g was found in TVSu – 174, while the least amount of 0.07 mg / g was found in TVSu – 1727.